N, P‐doped CoS2 Embedded in TiO2 Nanoporous Films for Zn–Air Batteries. (27th August 2018) - Guo, Limin; Deng, Jinan; Wang, Guanzhi; Hao, Yanan; Bi, Ke; Wang, Xiaohui; Yang, Yang
Abstract: The search for efficient and cost‐effective catalysts for bifunctional oxygen reduction and evolution reaction (ORR and OER) is highly demanded because of the sluggish four‐electron transfer involved redox reactions in Zn–air batteries (ZABs). Herein, (N, P) codoped CoS2 nanoclusters embedded inside TiO2 nanoporous films (denoted as N, P/CoS2 @TiO2 NPFs) are synthesized as novel bifunctional ORR/OER catalysts for ZABs. The catalytic activity and stability are promoted by the (N, P)‐dopants due to the enhanced conductivity, increased active surface area, and facilitated reaction kinetics. The N, P/CoS2 @TiO2 NPFs exhibit exceptional onset potentials of 0.91 and 1.41 V for ORR and OER, respectively. When used as cathodes in ZABs, the N, P/CoS2 @TiO2 NPFs exhibit a reduced charge–discharge gap of 0.8 V at 10 mA cm −2 and a stable cycling performance over 130 h, surpassing the conventional Pt/C+IrO2 catalysts. Moreover, the assembled ZABs delivering a specific capacity of 610 mAh g −1 can be used for flexible devices. This work provides a path for the rational design of bifunctional electrocatalyst for ZABs. Abstract : In this work, a concept of immobilizing CoS2 catalysts inside a chemically and structurally stable TiO2 nanoporous substrate for Zn–air batteries (ZABs) is presented. Such novel nanostructured film catalysts exhibit superior activities to conventional Pt group metal catalysts for catalytic reactions in ZABs.